2019
DOI: 10.3390/antiox8070231
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay Directed Isolation, Biological Evaluation and in Silico Studies of New Isolates from Pteris cretica L.

Abstract: Members of genus Pteris have their established role in the traditional herbal medicine system. In the pursuit to identify its biologically active constituents, the specie Pteris cretica L. (P. cretica) was selected for the bioassay-guided isolation. Two new maleates (F9 and CB18) were identified from the chloroform extract and the structures of the isolates were elucidated through their spectroscopic data. The putative targets, that potentially interact with both of these isolates, were identified through reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…Other than these, Asn237 and Asn241 also showed favorable H-bond occupancy of 40.9 and 23.8%. These molecular interactions were in-line with the reported experimental studies of f α-glucosidases [ 20 , 21 , 23 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 88%
“…Other than these, Asn237 and Asn241 also showed favorable H-bond occupancy of 40.9 and 23.8%. These molecular interactions were in-line with the reported experimental studies of f α-glucosidases [ 20 , 21 , 23 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 88%
“…Along with the outstanding performance of the network pharmacology in systems biology, the network pharmacologybased PharmMapper is increasingly popular in the field of drug research. Saleem et al found putative targets that potentially interact with 2 new maleates (F9 and CB18) of Pteris cretica L. through reverse docking by using the in-silico tools PharmMapper and ReverseScreen3D [19]. Zhang discovered the potential molecular targets of SQW treatment for KYDS through PharmMapper [20].…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial assay was performed via an agar well diffusion method. 30 All bacterial strains were inoculated into Mueller–Hinton broth for a period of 8 h. The pH was maintained at 7.4 during analysis. Cotton webs were utilized for seeding of isolated organism agar plates.…”
Section: Materials and Methodologymentioning
confidence: 99%